ANALISIS JARINGAN SYARAF TIRUAN UNTUK MENGETAHUI PENYEBAB DROP OUT PADA MAHASISWA - M. Fakhriza M. Fakhriza; Heri Santoso (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2018)
Drop-out is a form of failure to follow the students in the educational process at university. The number of students drop out in addition detrimental to the personal / individual, it is also detrimental to higher education institutions themselves. Therefore, it is necessary to study to find the causes or factors that affect student drop-out so it can be useful information for success in higher education. Methods backpropagation artificial neural network is a mathematical model that is used for the identification and classification based training and learning is done. In this study, backpropagation artificial neural network method used in identifying factors - factors causing the drop-out experienced by the students by making learning of the data - the data attributes of students drop out. Backpropagation artificial neural network implementation is done in this study produces good results where backpropagation artificial neural network can produce factors that cause dropouts appropriate to attribute a given student. Keywords: Artificial Intelligence, Artificial Neural Network, Backpropagation